FEATURES AND PROBLEMS OF IMPLEMENTATION OF INDIVIDUAL SOCIO-ECONOMIC DEVELOPMENT PROGRAMS OF THE SUBJECTS OF THE RUSSIAN FEDERATION - Землянский, Дмитрий; Чуженькова, Валерия; Абдуллаев, Александр; Калиновский, Леонид; Медведникова, Дарина; Прусихин, Олег (Public Administration Issues, 2024)
The article analyzes the features and problems of managing the implementation of individual socio-economic development programs (IDP), a special tool of regional policy implemented for 10 subjects of the Russian Federation with a low level of development for 2020-2024. The study is based both on the information from regulatory legal acts and reports on IDPs’ implementation, as well as on assessments of regional executive authorities and other interested parties, obtained from interviews conducted in two regions. They include IDP, public events with federal and regional authorities and departments’ responses to official requests for information. The results of the study showed that the existing management system of the IDP is overly complicated and does not work effectively enough, preventing the implementation of potentially significant regional projects. It was found that the procedure of the programs formation at the initial stage was violated, which later led to their repeated adjustments and then confusion in the timing, financing and understanding of the execution of program activities. The developed schemes for managing the implementation of individual programs in the regions vary and are significantly complicated by the inclusion of ministries-curators and several principal managers of budget funds. The low efficiency of the implementation of non-financial program activities was noted, but still a number of them play a significant role as a means of influencing decisions of federal authorities and a tool for launching larger projects. In the end recommendations for improving the management system of the IDP for the next five-year period are proposed.